Lan Station / Muhd Azfar Faieq Razali … [et.al.]. - Razali, Muhd Azfar Faieq; Jamal, Aliff; Sami, Mohd Hassan; Mohd Ghazali, Mohd Shalwan (2011)
LAN Station is the business which ventures on the cyber gaming and entertainment. This business has been agreed in the form of partnership, which consists of four partners. All partners have agreed to abide to all the terms of partnership as to contribute some capital according to the allocated shares. The main reason of existence the LAN Station is to provide entertainment on the latest computer platform games & massively multiplayer online role-playing games (MMORPG) to the public especially to the hardcore gamers. Today, many gamers are like to playing games with their partners in a group, but they have a problem on using LAN network or any problems that related. In addition, some of the computer games become more popular today such as Counter Strike & DotA & there are also some of the new and latest MMORPG that release and updated until now. But, there are some of the gamers that can't play their online games at their own PCs due to the server and broadband problems. From this problem, we will provide what they can't achieve with the best server and the best games for our customers.